Desvendando a segurança alimentar em tempos de crise: avaliação da Política de Segurança Alimentar e Nutricional em Fortaleza/CE no olhar do Consea municipal - Lins, Glenda Fernanda Alves Coelho (2024)
The research aimed to evaluate the Food and Nutrition Security Policy (PSAN) in Fortaleza, with emphasis on the period of the COVID-19 pandemic, from the perception of the members of the Municipal Council for Food and Nutritional Security (Consea/ Fortaleza). To do so, we sought to analyze the social, historical and political context that underlie the PSAN, investigating the conditions that led to its formulation and implementation, as well as the content of the policy, focusing on concepts of safety and nutritional insecurity. It also aimed to understand how the members of CONSEA mean food security and insecurity, as well as their perceptions about the beneficiaries of this policy. In a related perspective, it envisioned whether intersectionality - concept that describes how the social factors that define a person’s identity overlap and relate, affecting access to rights and the relationship with Society (Akotirene, 2020), was somehow present in its execution, considering the interactions between oppressions and social markers as social class, race, gender and territory. To do so, the approach of In-depth Evaluation was adopted, originally proposed by Rodrigues (2008), in order to allow a qualitative analysis focused on the experiences and narratives of the actors involved, with quantitative contributions of secondary nature. The results of the survey reveal that participants consider food security as a fundamental human right, essential for the dignity and well-being of people. This perspective implies the need to ensure regular and permanent access to quality food in sufficient quantity, respecting cultural diversity and promoting healthy eating practices. The research was carried out with the participation of the technical team and members of the Municipal Council for Food Safety and Nutrition of Fortaleza (Consea Fortaleza), selected randomly. The interviews, conducted individually, took place both in person and virtually, using a semi-structured script. For the analysis of data, the technique of Thematic Analysis was adopted, as proposed by Minayo (2005). Respondents highlight that it is not enough to have access to food alone; it is crucial that these foods are nutritionally adequate and safe, reflecting the importance of food quality as a central aspect of food security. In addition, the research indicates that food security is closely linked to other public policies such as social assistance and health. The implementation of effective policies is considered essential to meet the needs of vulnerable populations, suggesting that food insecurity is often a matter of socioeconomic inequality. Participants point out that food insecurity is a reflection of inadequate policies that do not meet the needs of underprivileged populations, highlighting the urgency of a more integrated and effective approach. Another critical point identified in the research is the lack of resources and a stable budget to finance food security initiatives, which is seen as a significant barrier to achieving the objectives of the National System for Food and Nutrition Security (SISAN). This budget limitation compromises the capacity to implement policies that guarantee the right to adequate food, perpetuating food insecurity among the most vulnerable populations. Also, the influence of politics in social assistance policies and the fragility of the Consea before these political conjunctures remained evidenced. Therefore, the research results emphasize the need for a renewed commitment and concrete actions to overcome these challenges, ensuring that food security is recognized and guaranteed as a right accessible to all. The final considerations highlight the complexity and challenges in the fight against hunger, especially during the pandemic context. Although the PSAN has moved from a narrow approach to a more integrated perspective, to recognize hunger as a social problem that requires structural interventions and the participation of civil society, There is still a long way to go before public policies can effectively promote equity and reduce inequalities.